2011 Design, Automation &Amp; Test in Europe 2011
DOI: 10.1109/date.2011.5763326
|View full text |Cite
|
Sign up to set email alerts
|

A global postsynthesis optimization method for combinational circuits

Abstract: Abstract-A genetic programming-based circuit synthesis method is proposed that enables to globally optimize the number of gates in circuits that have already been synthesized using common methods such as ABC and SIS. The main contribution is a proposal for a new fitness function that enables to significantly reduce the fitness evaluation time in comparison to the state of the art. The fitness function performs optimized equivalence checking using a SAT solver. It is shown that the equivalence checking time can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…This method led to a 25% area improvement with respect to the circuits heavily optimized by ABC [10]. As far as we know, no local evolutionary circuit resynthesis/optimization method has been proposed so far.…”
Section: Evolutionary Circuit Designmentioning
confidence: 94%
See 4 more Smart Citations
“…This method led to a 25% area improvement with respect to the circuits heavily optimized by ABC [10]. As far as we know, no local evolutionary circuit resynthesis/optimization method has been proposed so far.…”
Section: Evolutionary Circuit Designmentioning
confidence: 94%
“…It was shown that CGP can design and optimize various digital circuits [9] and improve results of conventional circuit synthesis and optimization tools [10]. In this work, we will utilize the standard CGP for combinational circuit evolution.…”
Section: Cartesian Genetic Programmingmentioning
confidence: 99%
See 3 more Smart Citations